2016
DOI: 10.1007/s10195-016-0431-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting outcome in whiplash injury: a systematic meta-review of prognostic factors

Abstract: BackgroundWhiplash injuries are among the leading injuries related to car crashes and it is important to determine the prognostic factors that predict the outcome of patients with these injuries. This meta-review aims to identify factors that are associated with outcome after acute whiplash injury.Materials and methodsA systematic search for all systematic reviews on outcome prediction of acute whiplash injury was conducted across several electronic databases. The search was limited to publications in English,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 29 publications
3
100
1
1
Order By: Relevance
“…For instance, some studies have reported that higher disability scores at baseline were associated with greater reduction in the same clinical outcome in subjects with whiplash‐associated neck pain after undergoing an exercise intervention . However, it is important to consider that cohort studies have shown that higher levels of pain intensity at baseline are a consistent factor for predicting poor outcomes in the same population . It is possible that the prognostic role of higher levels of pain and related disability would be different if patients underwent treatment vs. just following the natural history of the condition.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For instance, some studies have reported that higher disability scores at baseline were associated with greater reduction in the same clinical outcome in subjects with whiplash‐associated neck pain after undergoing an exercise intervention . However, it is important to consider that cohort studies have shown that higher levels of pain intensity at baseline are a consistent factor for predicting poor outcomes in the same population . It is possible that the prognostic role of higher levels of pain and related disability would be different if patients underwent treatment vs. just following the natural history of the condition.…”
Section: Discussionsupporting
confidence: 93%
“…40,41 However, it is important to consider that cohort studies have shown that higher levels of pain intensity at baseline are a consistent factor for predicting poor outcomes in the same population. 42,43 It is possible that the prognostic role of higher levels of pain and related disability would be different if patients underwent treatment vs. just following the natural history of the condition. Physical therapy: R 2 adjusted = 0.276 for step 1, R 2 adjusted = 0.312 for step 2.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that involvement by the insurance company could affect the outcome [10,11], but also that the compensation model [12] and the time from the MVA to claim closure play a significant role [13]. The "compensation hypothesis" suggests that the outcome is worse if financial compensation is given [14].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, people reporting severe pain may have few objective markers consistent with the report of pain (e.g., Lee et al., ). Thus, there appears to be a discordance between objective tests and pain reports and impact on functioning across such diverse disorders as back pain (Brinjikji et al., ; Lee et al., ), whiplash (e.g., traumatic injuries; Sarrami, Armstrong, Naylor, & Harris, ), and knee osteoarthritis (OA) (e.g., disease‐related; Finan et al., ; Thomas et al., ). Furthermore, identical surgical treatments may produce diverse reports of pain severity across individuals (e.g., Gerbershagen et al., ) and treatments targeting the same symptoms may have differing effectiveness across people with the same diagnosis (Rusu, Boersma, & Turk, ).…”
Section: The Biopsychosocial Perspective On Painmentioning
confidence: 99%
“…A wide variety of methodologies (experimental, case‐controlled cohort, longitudinal, cross‐sectional) have demonstrated a relationship between catastrophic thinking and measures of pain, psychological disability, physical disability, and gait velocity in patients with OA, response to surgery in the immediate post‐operative period (Roth, Tripp, Harrison, Sullivan, & Carson, ), as well as at 1‐year follow‐up (e.g., Riddle, Wade, Jiranek, & Kong, ; Sullivan et al., ), worsened pain experience overall (e.g., Arnow et al., ; Theunissen, Peters, Bruce, Gramke, & Marcus, ), and disability following traumatic injury (Sarrami et al., ). Furthermore, reductions in catastrophic thinking have been associated with symptom improvement (Smeets, Vlaeyen, Kester, & Knottnerus, ; Weissman‐Fogel, Sprecher, & Pud, ).…”
Section: Cognitive Aspects Of Painmentioning
confidence: 99%